2019
DOI: 10.2147/opth.s191635
|View full text |Cite
|
Sign up to set email alerts
|

<p>Six months' treatment with lifitegrast in patients with moderate-to-severe symptomatic dry eye: a retrospective chart review</p>

Abstract: Purpose To evaluate 6-month treatment benefits with lifitegrast ophthalmic solution 5% in symptomatic dry eye patients. Setting Retrospective chart analysis. Method A retrospective chart review was conducted in 168 patients (111 females and 57 males) who presented with symptoms of chronic dry eye disease and were treated with lifitegrast 5% ophthalmic solution for 6 months. Collected symptom data included improvement of eye dryness, tearing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Post hoc analysis of OPUS-2 and OPUS-3 trials stratified participants into four subgroups according to the severity of ICSS and EDS. The subgroup with an ICSS above 1.5 and an EDS of at least 60 at baseline (defined as moderate-to-severe DED) demonstrated a twofold-higher odds of achieving significant improvement [ 21 ]. In a retrospective study, 6 month treatment with lifitegrast significantly improved 56% of patients with moderate-to-severe symptomatic DED and moderately improved 36% of them [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc analysis of OPUS-2 and OPUS-3 trials stratified participants into four subgroups according to the severity of ICSS and EDS. The subgroup with an ICSS above 1.5 and an EDS of at least 60 at baseline (defined as moderate-to-severe DED) demonstrated a twofold-higher odds of achieving significant improvement [ 21 ]. In a retrospective study, 6 month treatment with lifitegrast significantly improved 56% of patients with moderate-to-severe symptomatic DED and moderately improved 36% of them [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, evidence supports the effectiveness of lifitegrast with concomitant artificial tear use in dry eye disease. 23 , 24 Future prospective studies may address whether the increase in natural tears and important biologically active beneficial constituents within human tears in response to OC-01 (varenicline solution) nasal spray treatment are affected or potentially washed out by concomitant use of artificial tears.…”
Section: Discussionmentioning
confidence: 99%
“…However, artificial tear use is usually continued in all stages of DED in conjunction with other treatments . Although artificial tear use was required to be discontinued before enrollment in the OPUS-2 and OPUS-3 studies, Atallah et al reported a significant improvement in the signs and symptoms of chronic DED with lifitegrast in a 6-month retrospective study, even in patients with concurrent use of artificial tears. In that study, most patients continued concomitant use of other DED treatments (79% used artificial tears) while receiving lifitegrast .…”
Section: Discussionmentioning
confidence: 99%
“…Although artificial tear use was required to be discontinued before enrollment in the OPUS-2 and OPUS-3 studies, Atallah et al reported a significant improvement in the signs and symptoms of chronic DED with lifitegrast in a 6-month retrospective study, even in patients with concurrent use of artificial tears. In that study, most patients continued concomitant use of other DED treatments (79% used artificial tears) while receiving lifitegrast . In the 1-year SONATA (Safety of a 5.0% Concentration of Lifitegrast Ophthalmic Solution) safety study, participants reported a decrease in the frequency of concomitant use of artificial tears during the 1-year period following treatment with lifitegrast .…”
Section: Discussionmentioning
confidence: 99%